Optimal synthetic conditions for oxetane-substituted chitosan (OXE-CHI) and polyethylene glycol (PEG) network self-healing agent - Li, Rui (2019)
In order to effectively repair cracks in the asphalt upon exposure to light, the paper studies the influence of distinctive chemically synthesized conditions of oxetane-substituted chitosan polyurethane (OXE-CHI-PUR) network self-healing agent for self-healing effect of asphalt at different pH values, doses of OXE and doses of catalyst to determine the optimal synthesis conditions. The study suggests that the optimall synthetic conditions for the self-healing agent include optimal pH = 6.8 , the optimum dose of OXE:CHI = 1:5 and the optimum dose of catalyst (dibutyl tin dilaurate) = 2%.